Wafer Surface Charge Reversal as a Method of Simplifying Nanosphere Lithography for Reactive Ion Etch Texturing of Solar Cells. (31st July 2007) - Inns, Daniel; Campbell, Patrick; Catchpole, Kylie
Abstract : A simplified nanosphere lithography process has been developed which allows fast and low-waste maskings of Si surfaces for subsequent reactive ion etching (RIE) texturing. Initially, a positive surface charge is applied to a wafer surface by dipping in a solution of aluminum nitrate. Dipping the positive-coated wafer into a solution of negatively charged silica beads (nanospheres) results in the spheres becoming electrostatically attracted to the wafer surface. These nanospheres form an etch mask for RIE. After RIE texturing, the reflection of the surface is reduced as effectively as any other nanosphere lithography method, while this batch process used for masking is much faster, making it more industrially relevant.